The common factor of the given expressions has to be determined.

x^2-x-6

= x^2 - 3x + 2x - 6

= x(x - 3) + 2(x - 3)

= (x + 2)(x - 3)

x^2 -5x +6

= x^2 - 3x - 2x + 6

= x(x - 3) - 2(x - 3)

= (x - 2)(x - 3)

**The common factor is (x - 3)**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now